Brain-Derived Neurotropic Factor Val66Met Polymorphism and Posttraumatic Stress Disorder among Survivors of the 1998 Dongting Lake Flood in China. (14th May 2017) - Dai, Wenjie; Kaminga, Atipatsa C.; Wu, Xin; Wen, Shi Wu; Tan, Hongzhuan; Yan, Junxia; Deng, Jing; Lai, Zhiwei; Liu, Aizhong
Abstract : Objective . This study mainly aimed to explore the association between brain-derived neurotropic factor (BDNF) Val66Met polymorphism and posttraumatic stress disorder (PTSD) among flood survivors in China. Methods . Individuals who experienced the 1998 Dongting Lake flood in Southeast Huarong, China, were enrolled in this study. Qualified health personnel carried out face-to-face interviews with participants. PTSD was identified using PTSD Checklist-Civilian version (PCL-C). Blood samples were collected from the participants to extract DNA for genotyping. Results . A total of 175 participants were enrolled in this study. The prevalence of PTSD among flood survivors at 17-year follow-up was 16.0% (28/175). Individuals with PTSD were more likely to be female, experience at least three flood-related stressors, experience at least three postflood stressors, and carry the Met than those without PTSD. Compared with Val/Val homozygotes, Met carriers had higher scores of PCL-C (mean ± standard error: 23.60 ± 7.23 versus 27.1 9 ± 9 . 48, P < 0.05 ). Multivariable logistic regression analysis indicated that Met carriers (aOR = 4.76, 95% CI = 1.02–22.15, P < 0.05 ) were more likely to develop PTSD than Val/Val homozygotes. Conclusions . Met carriers for BDNF rs6265 are at higher risk of developing PTSD and also exhibit more severe PTSD symptoms than Val/Val homozygotes among flood survivors in China.